Modulatory actions of Echinococcus granulosus antigen B on macrophage inflammatory activation - Folle, Ana Maite; Lagos Magallanes, Sofía; Fló, Martín; Alvez-Rosado, Romina; Carrión, Federico; Vallejo, Cecilia; Watson, David; Julve, Josep; González-Sapienza, Gualberto; Pristch, Otto; González-Techera, Andrés; Ferreira, Ana María (Frontiers in Cellular and Infection Microbiology, 2024)
Cestodes use own lipid-binding proteins to capture and transport hydrophobic ligands, including lipids that they cannot synthesise as fatty acids and cholesterol.In E. granulosus s.l., one of these lipoproteins is antigen B (EgAgB), codified by a multigenic and polymorphic family that gives rise to five gene products (EgAgB8/1-5 subunits) assembled as a 230 kDa macromolecule. EgAgB has a diagnostic value for cystic echinococcosis, but its putative role in the immunobiology of this infection is still poorly understood. Accumulating research suggests that EgAgB has immunomodulatory properties, but previous studies employed denatured antigen preparations that might exert different effects than the native form, thereby limiting data interpretation. This work analysed the modulatory actions on macrophages of native EgAgB (nEgAgB) and the recombinant form of EgAg8/1, which is the most abundant subunit in the larva and was expressed in insect S2 cells (rEgAgB8/1). Both EgAgB preparations were purified to homogeneity by immunoaffinity chromatography using a novel nanobody anti-EgAgB8/1. nEgAgB and rEgAgB8/1 exhibited differences in size and lipid composition. The rEgAgB8/1 generates mildly larger lipoproteins with a less diverse lipid composition than nEgAgB. Assays using human and murine macrophages showed that both nEgAgB and rEgAgB8/1 interfered with in vitro LPS-driven macrophage activation, decreasing cytokine (IL-1β, IL-6, IL-12p40, IFN-β) secretion and •NO generation. Furthermore, nEgAgB and rEgAgB8/1 modulated in vivo LPS-induced cytokine production (IL-6, IL-10) and activation of large (measured as MHC-II level) and small (measured as CD86 and CD40 levels) macrophages in the peritoneum, although rEgAgB8/1 effects were less robust. Overall, this work reinforced the notion that EgAgB is an immunomodulatory component of E. granulosus s.l.. Although nEgAgB lipid's effects cannot be ruled out, our data suggest that the EgAgB8/1 subunit contributes to EgAgB´s ability to regulate the inflammatory activation of macrophages.